A five-year follow-up study of antioxidants, oxidative stress and polyunsaturated fatty acids in schizophrenia. Issue 4 (10th August 2019) - Solberg, Dag K.; Refsum, Helge; Andreassen, Ole A.; Bentsen, Håvard
Abstract: Objective: Oxidative stress and dysregulated antioxidant defence may be involved in the pathophysiology of schizophrenia. In the present study, we investigated changes in antioxidants and oxidative stress from an acute to a later stable phase. We hypothesised that the levels of oxidative markers are increased in schizophrenia compared with healthy controls; change from the acute to the stable phase; and are associated with the levels of membrane polyunsaturated fatty acids (PUFAs) and symptom severity. Methods: Fifty-five patients with schizophrenia spectrum disorders, assessed during an acute phase and 5 years later during a stable phase, and 51 healthy controls were included. We measured antioxidants (α-tocopherol, uric acid, albumin and bilirubin), markers of oxidative stress (F2-isoprostane and reactive oxygen metabolites) and membrane fatty acids. Antioxidants and oxidative stress markers were compared in schizophrenia versus healthy controls, adjusting for differences in sex, age and smoking, and changes over time. Associations between symptoms and PUFA were also investigated. Results: In the acute phase, α-tocopherol was significantly higher ( p < 0.001), while albumin was lower ( p < 0.001) compared with the stable phase. Changes in α-tocopherol were associated with PUFA levels in the acute phase. In the stable phase, schizophrenia patients had higher uric acid ( p = 0.009) and lower bilirubin ( p = 0.046) than healthy controls. CRP was higher in patients in the stable phase ( p < 0.001), and there was no significant change from the acute phase. Conclusion: The present findings of change in antioxidant levels in the acute versus stable phase of schizophrenia the present findings suggest that redox regulation is dynamic and changes during different phases of the disorder.